The community forestry enterprise in Monarch Butterfly Region, Mexico: a business approach - Rodríguez-Zúñiga, Joel; González-Guillén, Manuel de J; Valtierra-Pacheco, Esteban (BOSQUE, 2019)
The absence of a consensus in the management of a community forestry enterprise can lead to inadequate management, inefficient use of resources and low competitiveness. To reverse this situation, it is important that people work in groups cooperating each other and achieving common goals, based on a set of shared informal norms and values called corporate principles. The objective of this research was to analyze the corporate principles of the forest communal enterprises in the Monarch Butterfly Biosphere Reservoir and their relation to the integration of the forest production chain and the conservation of natural resources. This research used structured and semi-structured surveys, a spatial analysis in a digital platform, and construction of a development index based on multivariate methods. Three enterprises with different levels of integration of the forest production chain were compared. Main findings showed that when the community enterprise integrates more segments into a forest production chain, members have better knowledge of the corporative principles. Forest community enterprises with higher productive integration have higher levels of conservation of their forestry, more economic benefits for their members and generate more social welfare for their community. It is recommended that public policies focused on forest communities should foster corporative culture to integrate adequately production chains of forest community enterprises.